Responding to climate change : lessons from an Australian hotspot - Burton, Paul (CSIRO Publishing, 2014)
South East Queensland has been one of the fastest growing regions of Australia, both in terms of its rapidly growing population and an ever-expanding built environment. It is also one of the most vulnerable regions likely to suffer from the adverse impacts of climate change, especially increased flooding, storms, coastal erosion and drought. Responding to Climate Change: Lessons from an Australian Hotspot brings together the results of cutting-edge research from members of the Griffith Climate Change Response Program, showing how best to respond to anticipated changes and how to overcome barri.